Nordic Families, Children and Early Childhood Education 2019
DOI: 10.1007/978-3-030-16866-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Initiatives in the Finnish Early Childhood Education Context

Abstract: Pedagogical practices in early childhood education, which embrace children's initiatives and agency, have been found to have an effect on children's learning and competence skills. These initiatives can be seen crucial for children's wellbeing and self-motivation; however, children's initiatives are sometimes considered only wants, and children incapable to express meaningful initiatives in educational settings. In this paper we introduce children's initiatives in their educational society and examine the gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, some findings exist. Kangas and Lastikka (2019) showed in their research about children's initiatives that children in ECE do not refer to their everyday activities and experiences as 'learning. ' However, the pre-primary class children referred in interviews to their new role as students whose role is to learn about new knowledge and things.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some findings exist. Kangas and Lastikka (2019) showed in their research about children's initiatives that children in ECE do not refer to their everyday activities and experiences as 'learning. ' However, the pre-primary class children referred in interviews to their new role as students whose role is to learn about new knowledge and things.…”
Section: Discussionmentioning
confidence: 99%
“…The role of children in Finnish legislation, education, and guiding documents has also changed during the past decade. The Nordic discourses in childhood especially emphasise the competent and active child, who has perceptions and interests, and who is an active agent of learning and wellbeing in their everyday life (Kangas and Lastikka 2019;Corsaro 2011). In the Nordic curricula, children are seen as active, competent, developing, and learning members of the educational society (Alasuutari, Markström, and Vallberg-Roth 2014).…”
Section: Introduction and Policy Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reciprocal participatory culture, adults see children as interesting persons who show initiative and have ideas, knowledge, views, and specific ways of acting that are considered worthy of examination. In this context, children have an influence on daily activities (see also Turja, 2016;Kangas, 2016;Kangas & Lastikka, 2019;Weckström et al, 2017). The supervising adult's views of an active child have an impact on the ideas and actions of the whole community.…”
Section: Conclusion: Communal Collaborative and Shared Social Partimentioning
confidence: 99%
“…Structures and practices in Finnish ECEC centres are deeply entrenched (Kangas, Venninen, & Ojala, 2016; Virkki, 2015). This creates challenges in promoting children's participation and including children's initiatives and interests (Kangas & Lastikka, 2019; Kirby, 2020). Furthermore, international research has shown that official documents and law do not automatically guarantee participation in ECEC practices (Connors & Morris, 2015; Kangas, 2016; Sargeant, 2018; Webb, 2015).…”
Section: Introductionmentioning
confidence: 99%